2018
DOI: 10.1111/jam.13662
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community changes in copper and PEX drinking water pipeline biofilms under extra disinfection and magnetic water treatment

Abstract: This study using rRNA showed that chlorination affects especially active fraction of bacterial communities. Copper and PEX differed by the occurrence of some bacterial members despite similar community profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…For instance, the family Sphingomonadaceae have been associated with antibiotic resistance 54 . In the current study, Novosphingobium, Sphingopyxis (members of this family) were more abundant in Medium-and High-chlorine regimes than the Low-regime, consistent with trends reported in chlorinated 17 and chloraminated 38 systems where Sphingomonadaceae taxa increased in abundance with increased disinfectant concentration. With respect to potential pathogens, Mycobacterium (a genus which includes opportunistic pathogens) were more abundant in the biofilms of a system with high chloramine concentration (3.8 ± 0.1 mgL −1 ) than a system with no residual (0.08 ± 0.01 mgL −1 ), despite being present at similar concentrations in the bulk water of each system 14 .…”
Section: Biofilm Microbiomesupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, the family Sphingomonadaceae have been associated with antibiotic resistance 54 . In the current study, Novosphingobium, Sphingopyxis (members of this family) were more abundant in Medium-and High-chlorine regimes than the Low-regime, consistent with trends reported in chlorinated 17 and chloraminated 38 systems where Sphingomonadaceae taxa increased in abundance with increased disinfectant concentration. With respect to potential pathogens, Mycobacterium (a genus which includes opportunistic pathogens) were more abundant in the biofilms of a system with high chloramine concentration (3.8 ± 0.1 mgL −1 ) than a system with no residual (0.08 ± 0.01 mgL −1 ), despite being present at similar concentrations in the bulk water of each system 14 .…”
Section: Biofilm Microbiomesupporting
confidence: 90%
“…Whilst chlorine has been shown to generally attenuate bacterial biofilm cell concentrations [16][17][18] , it is important to note that less, or no, inhibitory effect of chlorine has been reported for other taxa such as eukaryotes, particularly fungi 16,19,20 . Additionally, biofilmbound microorganisms have greater disinfection tolerance than their planktonic counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms in DWDS may harbor pathogens (WHO 2011; van der Wielen and van der Kooij 2013; Qin et al 2017) that may be causative agents of waterborne diseases (Gulati and Ghosh 2017). Biofilm development in DWDS is dependent on several factors, particularly nutrient availability, temperature, the characteristics of the adhesion surface, hydrodynamic conditions and the presence/concentration of disinfectants (Inkinen et al 2018). Materials typically used in DWDS, particularly in household and hospital plumbing, are comprised of plastics (for example, polyvinyl chloride-PVC, chlorinated PVC, polypropylene, polyethylene-PE, and polybutylene) and metallics (copper, galvanized iron, cast iron, galvanized steel) (WHO 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although copper is more expensive than plastics and other metallic pipes it is generally more resistant to corrosion, has no significant effects on the water quality, is easy to install and has antimicrobial properties ( _ Zabnie nska-G ora and Dudkiewicz 2018). The antimicrobial properties of copper materials may have an important action in preventing the build-up of biofilms in DWDS and the interest in its use is reemerging (Gulati and Ghosh 2017;Rhoads et al 2017;Assaidi et al 2018;Inkinen et al 2018;Khan et al 2019). Rhoads et al (2017) observed an important role of copper in L. pneumophila biofilm control in a stagnant DWDS.…”
Section: Introductionmentioning
confidence: 99%
“…22 The variability in the composition of copper alloys and consequently on the material characteristics does not facilitate the experimental design and the understanding of copper leaching phenomena. 27 Most of the works published about the use of copper in plumbing systems used elemental copper surfaces 14,16,[28][29][30] and did not present new alternatives to improve biolm prevention or to reduce possible leaching problems.…”
Section: Introductionmentioning
confidence: 99%